Gauging perceptions of ocean acidification in Alaska. (March 2015) - Frisch, L.C.; Mathis, J.T.; Kettle, N.P.; Trainor, S.F.
Abstract: While ocean acidification (OA) poses a significant threat to ocean-related ecosystems and communities reliant on marine fisheries, aquaculture, and coral reef systems, limited public understanding and awareness can prevent coastal regions from being able to adequately assess the need for OA adaptation or mitigation. This study assessed public understanding of OA and how social and demographic factors influence the public's concern for OA. The analysis was based on 311 questionnaires from full-time Alaska residents. The results showed that most Alaskans self-reported to have a basic awareness of OA, and subsequently were able to recognize that CO2 emissions related to human activity are the dominant driver of changing ocean conditions. However, there was a low recognition of how natural variability in the marine environment affects OA, and most respondents were not very confident in their understanding of OA-related science. Moreover, even though many communities in Alaska are reliant on commercial and subsistence fishing activities, the respondents had a low awareness of fisheries-related OA risk. Given the ongoing debate associated with climate change research, evaluating CO2 mitigation efforts through the perspective of OA could give individuals an unbiased way to assess the pros and cons of more intensive efforts to curb CO2 emissions. Furthermore, using OA communication to enhance the understanding of how natural variability influences OA around the state and the potential economic implications for Alaska fisheries would help residents and stakeholders make informed decisions when considering fisheries management plans, food security, and job diversity as OA intensifies. Solidifying the understanding that any reduction in pH and intensification of OA can have implications for marine species that are irreversible on human timescales will reinforce not only that OA is an immediate concern, but also the importance of taking action now. Highlights: Alaska seafood is a primary annual source of protein for 30 to 46% of respondents. Awareness of OA is about three times higher in Alaska than the rest of the US. Most respondents recognize CO2 and human activity as drivers of OA. Only 28% of respondents recognize that OA could disproportionately impact Alaska. Delayed concern for OA could delay willingness to adopt mitigation strategies.